Effect of carbon supports on RhRe bifunctional catalysts for selective hydrogenolysis of tetrahydropyran-2-methanol. Issue 21 (28th September 2016) - Karanjkar, Pranav U.; Burt, Samuel P.; Chen, Xiaoli; Barnett, Kevin J.; Ball, Madelyn R.; Kumbhalkar, Mrunmayi D.; Wang, Xiaohong; Miller, James B.; Hermans, Ive; Dumesic, James A.; Huber, George W.
Abstract : Orders-of-magnitude differences in hydrogenolysis activity were observed between RhRe/C catalysts with different carbon supports, which is due to the types of bimetallic particles that are formed on the different carbon supports. Abstract : Tetrahydropyran-2-methanol undergoes selective C–O–C hydrogenolysis to produce 1, 6-hexanediol using a bifunctional RhRe (reducible metal with an oxophilic promoter) catalyst supported on Vulcan XC-72 carbon (VXC) with >90% selectivity. This RhRe/VXC catalyst is stable over 40 h of reaction in a continuous flow fixed bed reactor. The hydrogenolysis activity of RhRe/VXC is two orders-of-magnitude higher than that of RhRe supported on Norit Darco 12X40 activated carbon (NDC). STEM–EDS analysis reveals that, compared to the RhRe/VXC catalyst, the Re and Rh component metals are segregated on the surface of the low activity RhRe/NDC catalyst, suggesting that Rh and Re in close proximity ("bimetallic" particles) are required for an active hydrogenolysis catalyst. Differences in metal distribution on the carbon surfaces are, in turn, linked to the properties of the carbons: NDC has both a higher surface area and surface oxygen content. The low areal density of Rh and Re precursors on the high area NDC and/or interactions of the precursors with its O functional groups may interfere with the formation of the bimetallic species required for an active catalyst.